Forced Exercise Preconditioning Attenuates Experimental Autoimmune Neuritis by Altering Th1 Lymphocyte Composition and Egress. (16th July 2015) - Calik, Michael W.; Shankarappa, Sahadev A.; Langert, Kelly A.; Stubbs, Evan B.
A short-term exposure to moderately intense physical exercise affords a novel measure of protection against autoimmune-mediated peripheral nerve injury. Here, we investigated the mechanism by which forced exercise attenuates the development and progression of experimental autoimmune neuritis (EAN), an established animal model of Guillain–Barré syndrome. Adult male Lewis rats remained sedentary (control) or were preconditioned with forced exercise (1.2 km/day × 3 weeks) prior to P2-antigen induction of EAN. Sedentary rats developed a monophasic course of EAN beginning on postimmunization day 12.3 ± 0.2 and reaching peak severity on day 17.0 ± 0.3 ( N = 12). By comparison, forced-exercise preconditioned rats exhibited a similar monophasic course but with significant ( p < .05) reduction of disease severity. Analysis of popliteal lymph nodes revealed a protective effect of exercise preconditioning on leukocyte composition and egress. Compared with sedentary controls, forced exercise preconditioning promoted a sustained twofold retention of P2-antigen responsive leukocytes. The percentage distribution of pro-inflammatory (Th 1) lymphocytes retained in the nodes from sedentary EAN rats (5.1 ± 0.9%) was significantly greater than that present in nodes from forced-exercise preconditioned EAN rats (2.9 ± 0.6%) or from adjuvant controls (2.0 ± 0.3%). In contrast, the percentage of anti-inflammatory (Th 2) lymphocytes (7–10%) and that of cytotoxic T lymphocytes (∼20%) remained unaltered by forced exercise preconditioning. These data do not support an exercise-inducible shift in Th 1:Th 2 cell bias. Rather, preconditioning with forced exercise elicits a sustained attenuation of EAN severity, in part, by altering the composition and egress of autoreactive proinflammatory (Th 1) lymphocytes from draining lymph nodes.